Foliar and twigs lesions of sweet orange caused by citrus leprosis - Marques, João Paulo Rodrigues; Astúa, Juliana de Freitas; Kitajima, Elliot Watanabe; Beatriz Appezzato-da-Glória, Beatriz (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to present the anatomical description of tissues lesioned by Citrus leprosis virus cytoplasmatic type (CiLV-C), in leaves and twigs of 'Pêra' sweet orange (Citrus sinensis (L.) Osbeck) providing new data to understand the interactions between the virus and the plant host, in Brazil. Leprosis lesions were cut on a rotary microtome (5–7 µm thick), stained and mounted in synthetic resin. For scanning electron microscope analysis, fixed tissues were immersed in glycerin 30% and criofractured, dehydrated in a graded ethylic series, critical point drying and coated with gold. Foliar lesions began as necrotic points surrounded by a yellow halo that inhibited the lesion expansion. The twigs presented two different lesions: depressed ones and pustules with ruptures. There was hyperplasia of the cortical and phloematic parenchyma cells causing the obliteration of phloematic vessels. These histological alterations of the phloem tissue could explain why the virus does not become systemic even occasionally infecting phloem parenchyma cells. The development of gummosis traumatic ducts in twig lesions was described here.